Monitoring biological and psychological measures throughout an entire season in male handball players - Bresciani, G.; Cuevas, M. J.; Garatachea, N.; Molinero, O.; Almar, M.; de Paz, J. A.; Marquez, S.; Gonzalez-Gallego, J. (European Journal of Sport Science, 2010)
The aim of this study was to monitor biological markers of inflammation and oxidative stress, mood states, and recovery-stress states throughout an entire season in male handball players. Fourteen handball players (age 20.1±2.5 years) with a regular training and competitive background in handball (11.0±3.7 years) from the same club volunteered to participate. All participants completed 40 weeks of training. The training load was increased progressively throughout the season. Blood samples were collected and questionnaires were administered during preparatory, competitive, and recovery periods. Blood C-reactive protein and oxidized glutathione (GSSG) concentrations increased during periods of high load, while the reduced/oxidized glutathione ratio (GSH/GSSG) decreased. These changes were accompanied by a significant increase in total leukocyte count. Positive correlations were found between C-reactive protein, GSSG, GSH/GSSG ratio, and training load. No changes were observed in the Total Mood Disturbance score of the Profile of Mood States (POMS). However, scores on some Recovery-Stress Questionnaire for Athletes subscales, such as Injury, Physical Recovery, and Being in Shape, correlated with training load. Findings indicate that during periods of high training load, handball players developed a low grade of inflammation and oxidative state. Results support the usefulness of monitoring psychological and biological markers of inflammation, oxidative stress, and training load during season.